Heterogeneous effects of forced migration on female labor supply - Julian Pedrazzi; Leonardo Pe\~naloza-Pacheco (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2021)
In this paper we analyze the impact of Venezuelan migration on the female labor supply in Colombia. Using a instrumental variable approach we found significant drops in the female labor supply, mainly on those women with lower qualifications. In contrast, we observe significant increases for high-skilled women with family responsibilities, such as childcare. These results are consistent with a redistribution of time use, where women spend fewer hours on household tasks and more time in the labor market. Our results provide novel evidence of the consequences of forced migration between developing countries on the female labor supply.
Keywords: F22; J22; J16; 330; Forced Migration; Female Labor Supply; Labor Market; Colombia; Venezuela